Ancient Egypt [videorecording (DVD)] : a journey back in time - Monserrat, Dominic; Baines, John, 1946-; Clayton, Peter; Gaballa, G. A. (Lost treasures of the ancient world., 2006)
This program visits, explores and restores the wonder as the Temple of Al Karnak and Luxor, the Temple of Abu Simnel and the Mortuary Temple of Hatsepsut.